2010
DOI: 10.1016/j.ultsonch.2010.03.003
|View full text |Cite
|
Sign up to set email alerts
|

On the physical origin of conical bubble structure under an ultrasonic horn

Abstract: The cavitation field generated by an ultrasonic horn at low frequency and high power is known to self-organize into a conical bubble structure. The physical mechanism at the origin of this bubble structure is investigated using numerical simulations and acoustic pressure measurements. The thin bubbly layer lying at horn surface is shown to act as a nonlinear thickness resonator that amplifies acoustic pressure and distorts acoustic waveform. This mechanism explains the self-stabilization of the conical bubble … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…A thin layer of bubbles is formed at the horn surface which impedes the sound field's propagation and causes a reduction in pressure amplitude beyond its formation. This has been confirmed with measurements of pressure amplitude when the bubble layer is the size of an acoustic half wavelength, in this instance the impedance suddenly drops [138]. It has been suggested that travelling waves are more prevalent for the horn and that transient bubbles dominate [44,48].…”
Section: Transducer Typesupporting
confidence: 59%
See 1 more Smart Citation
“…A thin layer of bubbles is formed at the horn surface which impedes the sound field's propagation and causes a reduction in pressure amplitude beyond its formation. This has been confirmed with measurements of pressure amplitude when the bubble layer is the size of an acoustic half wavelength, in this instance the impedance suddenly drops [138]. It has been suggested that travelling waves are more prevalent for the horn and that transient bubbles dominate [44,48].…”
Section: Transducer Typesupporting
confidence: 59%
“…Quasi acoustic streaming is caused by attenuation of the sound field, often influenced by the presence of bubbles causing the formation of an energy gradient in the direction of the fields propagation [135]. The radiation pressure as a result causes motion of the bubbles and an associated macroscopic flow (due to bubble motion and viscosity of the solution) in that direction [136][137][138]. Aside from influencing bubble dynamics, quasi acoustic streaming also reduces the degree of reflection of the sound field and distorts the standing wave component [117].…”
Section: Pressure Amplitudementioning
confidence: 99%
“…This fact has already been observed by the authors in other numerical and experimental works referred to bubbly media [16,9], in particular when waves interferences occur [17,10,13]. The nonlinear bubble vibration strongly affects the distribution of energy in the frequency domain but not the distribution of energy in space, which remains highly concentrated at the focus.…”
Section: Examplesupporting
confidence: 53%
“…The authors further proved theoretically that the acoustic amplitude of the emitted wave is strongly reduced by cavitation. In 2010, Debus and co-workers [8] explained the physical origin of CBS in terms of the amplification of acoustic pressure in a thin bubbly layer lying at the horn surface.…”
Section: Some Recent Related Results By Other Workersmentioning
confidence: 99%